KM TINGKAT PENGETAHUAN SERTA PENANGANAN WARMING UP DAN COOLING DOWN DENGAN KEJADIAN CEDERA PADA ATLET FUTSAL VENUS SEMARANG - Triyanita, Maya; Amanati, Suci; Jaleha, Boki (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2024)
In this service, we convey the importance of warming up and cooling down on the incidence of injuries in athletes. The warming up and cooling down on out must have the right duration and be effective. Through good knowledge, athletes can carry out injury prevention methods in accordance with the experience and knowledge gained. To determine the level of warming up and cooling down knowledge, it can be measured using a questionnaire and athlete screening (FMS examination). This service aims to share knowledge with athletes about what a warming up and cooling down is so that it can reduce the number of injuries in VENUS SEMARANG futsal athletes.